(untitled) (Conferencea, 2022)
Among the main factors that cause purulent-necrotic processes of the fingers among dairy cows brought from foreign countries in our country are the compression of animals, floor construction, violation of sanitary and hygienic norms, lack of exercise, the resistance of the organism to infection decreases due to the fact that the diet is not structured based on the components necessary for the life of the organism. the incidence rate is higher in spring months, where 31 heads (31.9%) of all registered cows, 28 heads (28.9%) in winter months, 21 heads (21.7%) in autumn months and 17 heads (17 It was found to be .5%).